Neutral- and Multi-Colored Semitransparent Perovskite Solar Cells - Lee, Kyu-Tae (Molecules, 2016)
In this review, we summarize recent works on perovskite solar cells with neutral- and multi-colored semitransparency for building-integrated photovoltaics and tandem solar cells. The perovskite solar cells exploiting microstructured arrays of perovskite “islands” and transparent electrodes—the latter of which include thin metallic films, metal nanowires, carbon nanotubes, graphenes, and transparent conductive oxides for achieving optical transparency—are investigated. Moreover, the perovskite solar cells with distinctive color generation, which are enabled by engineering the band gap of the perovskite light-harvesting semiconductors with chemical management and integrating with photonic nanostructures, including microcavity, are discussed. We conclude by providing future research directions toward further performance improvements of the semitransparent perovskite solar cells.